Investigation on enhancing strength and ductility of as-cast Mg-Gd-Y-Zn-Zr alloy by fine-tuning Zn/RE ratio - Yongfeng Li; Ang Zhang; Chuangming Li; Hecong Xie; Hengrui Hu; Bin Jiang; Yuyang Gao; Yuhong Cui; Zongliang Tan; Zhihua Dong; Fusheng Pan (Journal of Materials Research and Technology)
The Zn/RE ratio has a significant impact on the microstructure and mechanical properties of the as-cast Mg-Gd-Y-Zr alloys. In this work, the formation of microstructure in Mg-9Gd-3Y-xZn-0.5Zr is regulated through fine-tuning the Zn/RE ratio, and in-depth characterization and analysis are conducted to explore the influence of Zn/RE ratio on the strength and ductility. The effect of the LPSO phases, kinks, and {10 1‾ 2} twins enable the as-cast alloy with Zn/RE ratio of 0.25 to have ultimate tensile strength, yield strength, and elongation of 265.5 MPa, 164.3 MPa, and 7.4 %, respectively. In ''twin + kink'' mode, the twin stress is released through stress relaxation caused by kinks prevents premature cracking and improve strength. The increase in strength results from the LPSO phases hindering dislocations and kink strengthening. The improvement in ductility is attributed to the {10 1‾ 2} twins facilitating the grain deviation from hard orientations and the activation of non-basal <c+a> slip. This research deepens understanding of the strengthening and plasticizing mechanism in as-cast Mg-RE alloys, providing conditions for further enhancing the performance limits of heat-treated or deformed Mg-RE alloys.